Peningkatan Hasil Belajar Peserta didik Pada Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Course Riview Horay Berbantuan Media Video Animasi di Kelas III SDN 14 ATTS Kota Bukittinggi - Nadila Sonia; Elfia Sukma (Universitas Pahlawan Tuanku Tambusai, 2023)
This research begins with the low learning outcomes of students. The purpose of this research was to describe the Course Review Horay model in Class III SDN 14 ATTS Bukittinggi City in improving student learning outcomes. This research is a class action research (CAR) that uses qualitative and quantitative methodologies. It was carried out in two cycles, namely cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. In each cycle combines four stages, namely preparation, implementation, observation and reflection. The results showed an increase in: a) RPP Cycle I Meeting 1 with normal 77.27% (Enough), Cycle I Meeting 2 with normal 88.63% (Good), and Cycle II 95.45% (Very Good). b) implementation of the learning part of cycle I Meeting 1 with normal 79% (Enough), Cycle I Meeting 2 with normal 90.90% (Excellent), and Cycle II with normal 97.72% (Generally very good) Very Good). c) Student assessment in Cycle I meeting 1 with normal 75% (Enough), Cycle I Meeting 2 86.36% and Cycle II with normal 95.45% (Generally very good). From the results of the data above, it can be concluded that the Course Review Horay model is able to improve student learning outcomes.